ENHANCING LANGUAGE AWARENESS IN MULTILINGUAL EFL CLASSES - Budiwati, Tri Rina (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2018)
The fact that any language has its set of varieties serves to emphasise that it is important to have the right attitude and possess sufficient knowledge of the language to function in a multilingual society. Living in such a society, Indonesians must realize that an awareness needs to be created amongst EFL learners in the country about possessing the right attitude and knowledge of English, and this can only be done through the education system. This paper explores the concept of language awareness and links this specifically to methods of developing EFL awareness among multilingual students at the Ahmad Dahlan University in Yogyakarta, Indonesia. The study is grounded in Hawkins’ and Fairclough’s concepts of Critical Language Awareness, and its development and application by other experts. These basic concepts are employed to understand the significance of language awareness and the implications on EFL teaching methodology. The study reveals that Language Awareness undoubtedly has great significance for both EFL teachers and students. This paper proposes some ways to enhance students’ language awareness that could be applied in multilingual EFL classes.